Militância e afetividade política: um estudo com militantes operários do PSTU - Maria Gorete Antonia Mendes (2005)
This dissertation is to present the results of a research done with political activists, with the aim of analyzing the determinations of dedication to a political cause. Specifically, we seek to understand the life histories of political activists, researching in their stories the determinations of what we call "activist choice". We seek also to understand the subjective living of militants and the impact of political activism on their daily lives and on their affective and professional relationships. Not least, the connection between the individual histories and a social history made us possible a rapprochement with the trade union environment, in Minas Gerais, through the psychosocial aspects present in everyday trade union life. That the workers' action can change society is already an accepted fact in the social sciences. What often is forgotten is that these actions are based on affection: feelings and political passions. Thus, we could not perform an analysis of a political situation without taking into account the feelings and passions that keep these relations in permanence, conflicts and political commitments. So, despite the feelings and passions express themselves in an individual way, they actually refer to a dimension of historical reality. Hence, its importance for the understanding of political phenomena and their consequences in the social structure.